The pollution characteristics, source identification and health risks of multiple classes atmospheric SVOCs with complex emission sources of the petrochemical plant and other industries. (1st March 2023) - Xiang, Jun; Xu, Rongfa; Du, Dongwei; Tang, Bin; Yi, Miao; Cai, Fengshan; Yan, Xiao; Zheng, Jing; Li, Guiying; An, Taicheng
Abstract: SVOCs are ubiquitous air contaminants, whilst little was known about their environmental fates and sources in atmosphere in ambient areas around petrochemical and other industries. Herein, the levels of typical SVOCs, polycyclic aromatic hydrocarbons (PAHs), organophosphate flame retardants (OPFRs), polybrominated diphenyl ethers (PBDEs), phthalate acid esters (PAEs), and alternative plasticizers (APs), were investigated in atmosphere of residential areas around a petrochemical industry plant. The plant is bordering a developing metropolis, with highly developed modern industries and transportations. PAEs (128.7 ± 72.2 ng/m 3 ) were found with the highest levels in atmosphere, followed by APs (19.1 ± 14.6 ng/m 3 ), PAHs (13.6 ± 5.01 ng/m 3 ), OPRs (3.89 ± 1.85 ng/m 3 ), and PBDEs (0.08 ± 0.06 ng/m 3 ). Seasonal variation was observed for SVOCs in the particulate and gaseous phases ( p  < 0.05), with higher concentrations of PAEs, APs, and OPFRs in summer than winter, whereas the opposite for PAHs. Chemical properties of compounds will influence the G-P partitioning of SVOC in the atmosphere. The sources of SVOCs in the study area are complex, and mainly from plastics manufacturing (20.9%), chemical additive application (46.5%), and petroleum combustion (32.9%). The estimated lifetime lung cancer risk of PAHs was moderate in the residential areas, and was higher in winter than summer. In contrast, the incremental lifetime cancer risk for di (2-ethylhexyl) phthalate inhalation was below the acceptable level. The petrochemical plant was one of the primary sources of PAHs in the investigated area, posing a nonnegligible risk to the surrounding residents. This study enhanced our understanding of the environmental fates and health risks of multiple classes of SVOCs in atmosphere with complex emission sources near the petrochemical plant and other industries. Graphical abstract: Image 1 Highlights: Air SVOCs in residential areas around a petrochemical plant was analyzed. Significant seasonal differences were observed for air SVOC levels. Chemical properties significantly influenced the gas-particle partitioning of SVOCs. A moderate risk was found for air PAHs, which was higher in winter than in summer. The incremental lifetime cancer risk of inhalation exposure to DEHP was acceptable.